Impact of venture capital investment syndication on enterprise lifecycle and success - Siddiqui, A.; Marinova, Dora; Hossain, A. (Canadian Center of Science and Education, 2016)
The article investigates the impact of venture capital investment and investment syndication on enterprise lifecycle and success using the exit history of venture capital backed companies in Australia. It is observed that the venture capital backed companies tend to outperform those which are not while companies receiving syndicated venture capital investment tend to outperform the other venture capital backed companies. Based on the classic venture capital investment theory, we argue that venture capitalists essentially engage in superior venture selection through pre-investment screening and contribute to entrepreneurial development through post-investment monitoring and value creation. We then empirically investigate the lifecycle of the Australian venture capital backed companies from company formation to first venture capital financing round to exit. Survival duration of the ventures, investment growth and exit status are specifically analysed to capture the lifecycle. The findings show that the survival duration prior and post venture capital investment, venture capital investment growth in successive rounds and investment syndication increase the probably of success for the ventures.